Flexible piezoresistive sensors based on "dynamic bridging effect" of silver nanowires toward graphene. (March 2017) - Wei, Yong; Chen, Song; Dong, Xuchu; Lin, Yong; Liu, Lan
Abstract: The essence of piezoresistive sensors is the variation in charge transport property under external mechanical stresses (compression, bending, twisting, et al.), thus how to build such difference in charge transport property before and after external loadings is crucial to design high performance piezoresistive sensors. In the current study, a bio-based flexible piezoresistive sensor based on the "dynamic bridging effect" of silver nanowires (AgNWs) toward reduced graphene oxide (rGO) is presented, in which the highly conductive welded AgNWs networks cross and bridge the neighboring high-resistive grain boundaries and rGO contacts when applied with mechanical stresses. The variation of the charge transport behavior results in drastic decrease in resistance even under subtle loadings. The obtained piezoresistive sensor shows high sensitivity (5.8 kPa −1 ), fast response and relaxation properties (29.5 ms and 15.6 ms, respectively), ultralow detection limit (0.125 Pa) and excellent stability (>10000 loading/unloading cycles). The high performance piezoresistive sensor demonstrates great potentials in detection of wrist pulse waves, smart wearable electronics, monitoring or simulation of human body's motions and movements. Graphical abstract: